2003
DOI: 10.1029/2002gl015981
|View full text |Cite
|
Sign up to set email alerts
|

Low‐frequency continuous tremor around the Moho discontinuity away from volcanoes in the southwest Japan

Abstract: Recent enhancement of seismic networks in the Japan Islands revealed occurrence of low‐frequency continuous tremors of a beltlike distribution in the southwest Japan, where the subducting Philippine Sea plate reaches depths of 30–40 km. Source depth of the tremor is estimated by selecting tremor segments with relatively clear P‐wave onsets. The source region of the tremor is assumed to correspond to lowermost parts of crust close to a triple boundary of the crust, mantle wedge, and the subducting slab. The lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
229
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(233 citation statements)
references
References 8 publications
4
229
0
Order By: Relevance
“…This proposal is supported by the results of other studies (e.g. Katsumata and Kamaya, 2003;Seno and Yamasaki, 2003). Furthermore, Matsubara et al (2008) attributed the origin of DLTs to high pore pressures in the high-V p /V s area, arising from the release of water via dehydration reactions.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This proposal is supported by the results of other studies (e.g. Katsumata and Kamaya, 2003;Seno and Yamasaki, 2003). Furthermore, Matsubara et al (2008) attributed the origin of DLTs to high pore pressures in the high-V p /V s area, arising from the release of water via dehydration reactions.…”
Section: Discussionsupporting
confidence: 80%
“…Archie, 1942;Kariya and Shankland, 1983;Nesbitt, 1993;Glover et al, 2000). The MT method (Cagniard, 1953;Kaufman and Keller, 1981;Vozoff, 1991) is one of the most promising approaches in determining the nature of subsurface conductivity structures. Fuji-ta et al (1997) carried out a wide-band MT survey at eight sites along a NNW-SSE profile across the Kii Peninsula and presented a two-dimensional (2-D) conductivity model for the shallow-middle crust (up to 20 km in depth).…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the above detrended time series, our filtering analysis shows that interplate aseismic slip occurred in the period between May and September 2009 beneath the Bungo Channel and southwest Shikoku, covering a low-frequency earthquake area (Fig. 5(b)) (Katsumata and Kamaya, 2003). The interplate aseismic slip for this period is much larger than 1σ error as shown in Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Analyses using propagation velocity (Obara 2002;Katsumata and Kamaya 2003), polarization (La Rocca et al 2005Wech and Creager 2007), and stacked waveform Shelly et al 2006Shelly et al , 2007 suggested that non-volcanic tremors consist of many overlapping S-waves radiating from lowfrequency earthquakes (LFEs). The waveforms of each tremor investigated in this study are characterized by obscure phase arrivals and long durations, suggesting superposition of small events.…”
Section: Focal Mechanism Of the Tremorsmentioning
confidence: 99%